2005
DOI: 10.1590/s1806-83242005000100013
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial analysis of the Tweed Foundation in Angle Class II, division 1 malocclusion

Abstract: ABSTRACT:This study has defined the cephalometric values of the Craniofacial Analysis of the Tweed Foundation for a sample of Brazilian subjects. The sample consisted of 211 cephalometric radiographs from subjects aged 12-15, which were divided into two groups: Class II group, with 168 lateral teleradiographs (cephalograms) of white Brazilian subjects, with Angle Class II, division 1 malocclusion, of both genders (82 males and 86 females); and the Control Group, with 43 lateral teleradiographs (cephalograms) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…6,7,9,[17][18][19] Class II division 1 subjects present anteroposterior discrepancies, which could determine proclined maxillary anterior teeth with a large overjet as well as lingual displacement of second molars due to mandible with inadequate space. 17,18 Furthermore, they might have a hyperdivergent skeletal pattern, with a steep mandibular plane angle and a long anterior lower face height with open bite tendency. 6 These characteristics, depending on malocclusion severity, may eventually determine the lack of anterior 6 or mandibular second molar contacts, thus decreasing the number of occlusal pairs.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,9,[17][18][19] Class II division 1 subjects present anteroposterior discrepancies, which could determine proclined maxillary anterior teeth with a large overjet as well as lingual displacement of second molars due to mandible with inadequate space. 17,18 Furthermore, they might have a hyperdivergent skeletal pattern, with a steep mandibular plane angle and a long anterior lower face height with open bite tendency. 6 These characteristics, depending on malocclusion severity, may eventually determine the lack of anterior 6 or mandibular second molar contacts, thus decreasing the number of occlusal pairs.…”
Section: Discussionmentioning
confidence: 99%
“…Quanto ao tipo de desproporção esquelética, estudou-se a do tipo Classe II por ser apontada por alguns estudos como a mais incidente no Brasil 9,10 . Para tanto, essa pesquisa correlacionou teoricamente as alterações do crescimento craniofacial do tipo Classe II, quando associada à classe II de Angle, e sua relação com as alterações miofuncionais.…”
Section: Introductionunclassified
“…P Bhattarai et al 17 found FMA mean value of 28 degrees in Nepalese and P.C. Tukasan et al 16 found FMA mean value 26.66 degree on Brazilian subjects.…”
Section: Resultsmentioning
confidence: 97%